Blood Flow Modeling to Improve Cardiovascular Diagnostics: Application of A GTF to Predict Central Aortic Pressure using a 1-D Model - T. Butt, A.; A. Abakr, Y.; B. Mustapha, K. (International Journal of Engineering and Technology, 2018)
This study aims to demonstrate that a comprehensive one-dimensional model of the arterial network can be used in conjunction with the generalized transfer function (GTF) technique to estimate central aortic pressure using pressure waveforms obtained from peripheral sites. The peripheral and central pressure waveforms for a healthy subject are used to estimate transfer functions, which are then used to reconstruct central aortic pressure waveforms for a second model that simulates arterial stiffening. The similarities between the simulated aortic waveform and the waveforms estimated using the transfer function are and Â from the brachial, carotid and iliac arteries, respectively. The root-mean-square errors (RMSE) for the reconstructed waveforms from the brachial, carotid and iliac arteries are and Â mmHg, respectively. The results from this study illustrate that the proposed method provides a feasible alternative to higher dimensional models as well as experimental studies and can greatly enhance the accuracy of central aortic pressure estimation.Â Â Â Â Â